2013
DOI: 10.3141/2393-08
|View full text |Cite
|
Sign up to set email alerts
|

Feature Analysis and Operation Evaluation of Pedestrian Weaving Zone

Abstract: Weaving behavior occurs because of the conflict of pedestrian walking streams, and such behavior manifests itself as weaving points in walking facilities. If many weaving points are concentrated in a relatively stable zone, the zone is defined as a pedestrian weaving zone (PWZ). Weaving behavior has a great impact on pedestrians’ speed and walking comfort, facility capacity, and passenger safety. First, both the concept of the PWZ and PWZ features are defined. By means of controlled experiments, data on weavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Empirical approaches for understanding complex pedestrian crowd behaviours such as turning (Dias et al, 2014), crossing (Helbing et al, 2005;Asano et al, 2009;Dias et al, 2013) and weaving (Wu and Lu, 2013) have been conducted in the past to study collective pedestrian dynamics. However, regarding merging crowd flows, experimental studies (and also modelling) is limited in literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical approaches for understanding complex pedestrian crowd behaviours such as turning (Dias et al, 2014), crossing (Helbing et al, 2005;Asano et al, 2009;Dias et al, 2013) and weaving (Wu and Lu, 2013) have been conducted in the past to study collective pedestrian dynamics. However, regarding merging crowd flows, experimental studies (and also modelling) is limited in literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, we highlight diverging behavior as a gap in the empirical study of crowd dynamics. However, regarding a theoretical approach, Wu and Lu (2013) conducted a simulation study case of diverging behavior using Legion software in the application part of their weaving studies and found that an improved design in passageways exits (converted square corners to smoothed ones) could reduce the weaving points in the weaving zone of diverging flows, thereby increasing the flow rate of passageways.…”
Section: Multi-directional Flowsmentioning
confidence: 98%
“…The difference between entering a door and diverging flows lies in the stabilities of these flows. Unlike the fluctuating flows around a bottleneck, the streams of pedestrians are stable both before and after diverging processes (Wu and Lu, 2013).…”
Section: Multi-directional Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation curve proved that the weaving behavior evolved into three basic states (begin, spread and dissipated) but the threshold values of each state were not concerned in this paper. In Wu and Lu's study [18], some controlled experiments were applied to grasp the influence of walking condition on pedestrian weaving flows; the test result shows that the speed of in weaving area is significantly lower than before and after weaving, which is decreased by 10% to 35%. Weng and Feng [19] built a simulation platform to simulate unidirection weave pedestrian from volume, density, and other feature parameters.…”
Section: Literature Reviewmentioning
confidence: 99%